Visualisasi Data Penjualan Barang Retail di Seluruh Dunia Menggunakan Tableau - Salmah Nur Zahra; Pradita Eko Prasetyo Utomo (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
In recent years, electronic commerce or e-commerce has experienced significant growth worldwide. Retail companies utilize e-commerce platforms to sell their products to customers in various countries. In this context, a good understanding of sales data and trends in the global market becomes crucial for optimizing marketing strategies and improving sales performance. Data visualization plays a vital role in transforming complex sales data into easily understandable graphs, charts, and tables. Tableau, as a popular data visualization tool, aids retail companies in creating appealing and informative dashboards, understanding global sales trends, identifying business opportunities, and making evidence-based decisions. In this research, descriptive analysis is used to provide a concise and detailed overview of sales data in the global retail industry. The visualization results using Tableau reveal that New Zealand is the country with the highest sales, the year 2014 had the highest sales, and personal care products are the most purchased items by consumers. This research provides valuable insights for retail companies to optimize their marketing strategies and make better-informed decisions based on a deeper understanding of their sales data.